Reversible Myocardial Depression and Dilatation in COVID-19 Shock Patients - Matthew J. Fata, DO; Steven M. Hollenberg, MD; Brent Klinkhammer, MD; David Landers, MD; George Rockett; Jana Tancredi; Zoltan Turi, MD; Joseph E. Parrillo, MD (Critical Care Explorations)
IMPORTANCE:. A characteristic pattern of bacterial and fungal septic shock is decreased left ventricular (LV) ejection fraction (LVEF) and modest dilatation of the LV. In survivors, the myocardial depression and dilatation are reversible within several days. In a cohort of 368 hospitalized COVID patients with shock from March 2020 to December 2021, 15 patients were identified with an echocardiogram determined depressed LVEF during acute shock, and a follow-up echocardiogram was performed. OBJECTIVES:. Myocardial dysfunction and dilatation associated with COVID-19 are reversible. DESIGN, SETTING, AND PARTICIPANTS:. LVEF was determined by Simpson’s rule and stroke volume (SV) was analyzed by Doppler. Based on the LVEF and cardiac index (CI), patients were categorized into groups with low or normal values using an ejection fraction of 45% and CI 2.2 L/min/m2 as the respective thresholds. A subset of 15 patients underwent serial echocardiography, which was performed at a median of 13 days (95% CI, 9–39 d) after the initial value. MAIN OUTCOMES AND MEASURES:. The LVEF and LV volumes recorded during initial and follow-up echo were analyzed using paired t test. RESULTS:. Comparing initial during acute shock with follow-up values, the mean (± sd) LVEF was 35.3 ± 8.1 vs. 43.8 ± 3.47 (p = 0.031), indexed SV 29.6 ± 1.9 mL vs. 31.7 ± 2.3 mL (p = 0.522), LV end-diastolic volume 182 ± 14.1 mL vs. 152.1 ± 12.9 mL (p = 0.025), and LV end-systolic volume 120.2 ± 13.1 mL vs. 90.1 ± 12.1 mL (p = 0.025), respectively. CONCLUSIONS AND RELEVANCE:. Serial echocardiographic studies of COVID-19 shock patients with reduced LVEF and ventricular dilatation demonstrate reversibility of myocardial depression and dilation with no change in SV, a finding strikingly similar to that seen in bacterial and fungal-induced septic shock. Thus, COVID-19 (viral) induced septic shock may have a similar pathogenetic mechanism of myocardial dysfunction to that seen with bacterial or fungal sepsis.